Development of Learning Media Based on PLORA Animation Videos on Students’ Thinking Skills Social Arithmetic Material Class VII Junior High School - Annisa Kinanthi Sari; Hesti Rahmasari*; Supardi Uki Sajiman (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
The laziness and coverage of the material as well as the boredom of students when watching learning videos need a solution. This study aims to develop PLORA animated video-based learning media on students' thinking skills of class VII social arithmetic material. This research applies Research and Development (RD) research and development procedures by applying the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This media was developed with 3D animation video PLORA software to improve students' thinking skills. The research was conducted at SMPN 20 South Tangerang City. The practicality test of PLORA animation-based learning media was analyzed through a small class test with 5 students and a large class test with 28 students and 1 mathematics teacher. The results showed that the average validity test score by material and media experts was 83.76% and 92.37% so that overall validation obtained very valid criteria. The results of the small class trial showed a positive response from the subject and the results of the large class trial students obtained a score of 85.11% with very practical criteria and the teacher obtained a score of 80% with practical criteria. The development of PLORA animated video-based learning media on students' thinking skills in class VII junior high school social arithmetic material can be said to be valid and practical to be applied in the implementation of the mathematics learning process.Keywords: Learning Media, Animated Video, Social Arithmetic Material Rasa malas dan cakupan materi yang banyak serta kebosanan siswa pada saat menonton video pembelajaran perlu suatu solusi. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis video animasi PLORA pada kemampuan berpikir siswa materi aritmatika sosial kelas VII. Penelitian ini menerapkan prosedur penelitian dan pengembangan Research and Development (RD) dengan mengaplikasikan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Media ini dikembangkan dengan video animasi 3D software PLORA untuk meningkatkan kemampuan berpikir siswa. Penelitian dilaksanakan di SMPN 20 Kota Tangerang Selatan. Uji kepraktisan media pembelajaran berbasis animasi PLORA dianalisis melalui uji kelas kecil dengan 5 siswa dan uji kelas besar dengan 28 siswa dan 1 guru matematika. Hasil penelitian menunjukkan bahwa rata-rata skor uji kevalidan oleh ahli materi dan media sebesar 83,76% dan 92,37% sehingga secara keseluruhan validasi memperoleh kriteria sangat valid. Hasil uji coba kelas kecil menunjukkan respon yang positif dari subjek dan hasil uji coba kelas besar siswa memperoleh skor 85,11% dengan kriteria sangat praktis dan guru memperoleh skor 80% dengan kriteria praktis. Pengembangan media pembelajaran berbasis video animasi PLORA pada kemampuan berpikir siswa materi aritmatika sosial kelas VII SMP dapat dikatakan valid dan praktis untuk diterapkan dalam pelaksanaan proses pembelajaran matematika.